AUDIOVISUAL HELPING TEACHER AND STUDENTS IN TEACHING LEARNING PROCESS OF SOCIAL SCIENCES SUBJECT AT SDN 024868 BINJAI - Eti Muliani (VISION, 2018)
This study is categorized as a classroom action research that aims to improve the students of learning outcomes in State Primary School 024868 Binjai at Grade VI students by using audiovisual, academic year 2016/ 2017. This study is a collaborative research which is conducted in two cycles using the two methods of data collection which are observation and questionnaire. The data is first collected and then analyzed by the analysis of qualitative data through two stages, namely the presenting the data and drawing the conclusions. Qualitative analysis is then fitted with a descriptive analysis using quantitative percentage to calculate the score Social Sciences subject activities. Based on the results of the study, it can be concluded that the implementation of Audiovisual can improve Social Sciences Learning Activities of the students of Grade VI. It is evidenced by an increasing score on Social Sciences Learning Activities of the students’ of Grade VI. It increased from 60% in the first cycle to 90% in the second cycle.Keywords: Social Sciences, Audiovisual as Media in Improve Students Learning Outcomes